THE ROLE OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN PROVIDING EMPLOYMENT - PhD Sh.Z.Muxitdinov; Ergashev Jahongir Toshpolat ogli (Scholar Express Journal, 2022)
In this article, the role of small business and private entrepreneurship in increasing employment and income of the population is highlighted, various social assistances were provided to the population on the basis of "Every family is an entrepreneur", "Our youth is future" and other social programs. The following main directions of wide involvement of the population, especially young people and women in entrepreneurship, improvement of the microfinancing system and state support of entrepreneurship have been developed
Keywords: Small business; private entrepreneurship; population employment; entrepreneurship